Digital gamification in higher education: Kahoot as a learning tool for Indonesian discourse - Nurulanningsih, Nurulanningsih; Wulandari, Astriana; Suryadi, Edi; Amalia, Falina Noor; Agustina, Aryanti; Dayanti, Astri Nopi (Indonesian Research Journal in Education |IRJE|, 2026)
This study examines university students’ perceptions of Kahoot-based digital gamification in Indonesian discourse learning. As higher education increasingly integrates educational technology, gamified platforms such as Kahoot are widely adopted to enhance engagement and learning motivation. However, limited research has specifically examined its role in tertiary-level discourse learning in Indonesia. Employing a descriptive quantitative approach, this study involved 20 sixth-semester students from the Indonesian Language and Literature Education Program at Tridinanti University. Data were collected using a validated Likert-scale questionnaire and analyzed using descriptive statistics. The findings reveal predominantly positive perceptions across three dimensions: self-perception, interpersonal perception, and situational perception. Students reported increased motivation, participation, confidence, and classroom enjoyment. The results suggest that Kahoot supports interactive learning and fosters a more engaging academic environment. This study contributes to the growing body of research on digital gamification in higher education and offers pedagogical implications for technology-enhanced language instruction.